Potent Vasodilator and Cellular Antioxidant Activity of Endemic Patagonian Calafate Berries (Berberis Microphylla) with Nutraceutical Potential - Garcia Huidobro-Toro, J; Calfio-Painemal, C (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Hydroalcoholic extracts of Patagonian Calafate berry (Berberis microphylla) contain mono or disaccharide conjugated anthocyanins and flavonols. The Liquid Chromatography-Mass Spectrometry (LC-MS) chemical extract profile identified glycosylated anthocyanidins such as delphinidin-, petunidin- and malvidin-3-glucoside as the major constituents. The predominant flavonols were 3-O substituents quercetin-rutinoside or -rhamnoside. Anthocyanins doubled flavonols in mass (13.1 vs. 6 mg/g extract). Polyphenols vascular actions were examined in the rat arterial mesenteric bed bioassay; extract perfusion elicited concentration-dependent vasodilatation mimicked by conjugated anthocyanins standards. Vascular responses of main glycosylated anthocyanins were endothelium-dependent (p < 0.001) and mediated by NO production (p < 0.05). The anthocyanins antioxidant activity determined in isolated endothelial cells (CAA) showed a reduced redox potential as compared to the extract or quercetin. While in the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay, the anthocyanins showed an equivalent quercetin potency, the extract was 15-fold less active, proposing that the anthocyanin-induced vasodilation is not due to an antioxidant mechanism. The extract shows promising commercial nutraceutical potential. © 2019 by the author